Nano g∗α -Homeomorphisms in nano topological spaces (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In This Paper, We Introduce Ng∗Α -Open And Closed Maps In Nano Topological Spaces And Also We Introduce And Study The Concept Of Ng∗Α -Homeomorphisms In Nano Topological Spaces. Further We Obtain Certain Charecterizations Of These Maps.